Tarbiyatul Aulad Fil Islam: Pemutus Mata Rantai Prilaku Menyimpang di Kalangan Remaja - Saputra, Doni (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Sexual deviance among students is a serious challenge in today's world of Education. This study aims to evaluate and detail the implementation of the book "Tarbiyatul Aulad Fil Islam" in SMK Al-Ikhlas as an effort to deal with sexual perversion among students. The research method used is a qualitative approach by observing, interviewing, and analyzing documents related to the implementation of the book in schools. The results obtained are (1) deviant behavior of adolescents in SMK Al-Ikhlas of particular concern is the deviation of sexual behavior in the form of excessive courtship, verbal-nonverbal sexual harassment, viewing and storing pornographic videos that affect one of the students who are pregnant out of wedlock. (2) the development process of learning the book of Tarbiyatul Aulad at SMK Al-Ikhlas began in 2018, with the flow of the school formulating problem-solving, determining the books used, determining the methods used, determining the lessons to be made collaboration, ensuring the contents of the book can be applied effectively, involving parents in the process, seeing the challenges and obstacles in the process, involving all teachers and staff employees as effective facilitators, and periodic evaluation and review. (3) the implications of the implementation of the book of Tarbiyatul Aulad in deciding deviant behavior among adolescents SMK Al-Ikhlas very successful and got a lot of positive responses from various parties and will be evaluated and defended as an alternative character education material in practical, theoretical, philosophical and academic for students SMK Al-Ikhlas and other teenagers in general